Implementation of Diagnostic and Formative Assessments in English Language Learning Based on the Merdeka Curriculum - Muhammad Husaini (CV. Edujavare Publishing, 2024)
The implementation of diagnostic and formative assessment is an important aspect of English language learning within the Merdeka Curriculum, particularly because the curriculum emphasizes student-centered learning, differentiation, flexibility, and competency development. This study aims to examine the implementation of diagnostic and formative assessments in English language learning based on the principles of the Merdeka Curriculum and to identify their contribution to improving the learning process. This study employed a Systematic Literature Review (SLR) approach by identifying, selecting, evaluating, and synthesizing relevant scholarly literature concerning diagnostic assessment, formative assessment, English language learning, and the Merdeka Curriculum. The findings indicate that diagnostic assessment provides teachers with important information regarding students’ initial competencies, prior knowledge, learning difficulties, and language proficiency, which can be used to determine appropriate learning strategies and differentiated instruction. Meanwhile, formative assessment supports continuous monitoring of students’ progress through questioning, observation, assignments, quizzes, self-assessment, peer assessment, and feedback. The review also indicates that effective feedback and the appropriate utilization of assessment results are essential for improving students’ English language competencies and developing their self-regulated learning. Nevertheless, the implementation of these assessments may face challenges related to teachers’ assessment literacy, time constraints, classroom size, instrument development, and the interpretation and utilization of assessment results. Overall, diagnostic and formative assessments can strengthen the implementation of the Merdeka Curriculum by transforming assessment from a final measurement instrument into an integral component of learning that supports differentiated, responsive, and student-centered English language instruction.